The effect of domestication and ontogeny in swine cognition (Sus scrofa scrofa and S. s. domestica) - Albiach-Serrano, Anna; Bräuer, Juliane; Cacchione, Trix; Zickert, Nele; Amici, Federica (Applied animal behaviour science, 2012)
Domesticated animals show physical, behavioural and cognitive differences from their closest wild relatives. This may have resulted from the former's long and continued selection by humans throughout history, but in some cases it could just reflect developmental differences between wild and domestic animals, given that their environments usually differ significantly. In order to investigate possible effects of domestication and ontogeny on swine cognition, we tested wild boars and two groups of domestic pigs living in more and less enriched conditions. In an object choice paradigm subjects had to find food hidden in one of two containers. They received either a physical cue (i.e., the slope of the board hiding the food, the presence or absence of noise from a shaken container, the sight of a baited container changing position) or a human social cue (i.e., touching, pointing, gazing). According to the domestication hypothesis, given similar rearing conditions domestic pigs should perform better than wild boars when receiving social cues but worse when receiving physical cues. According to the developmental hypothesis, more experienced swine should perform better than less experienced swine both in the physical and in the social domain. Subjects performed better when provided with cues on which they had received adequate experience from their environment, thus providing support to the developmental hypothesis. We conclude by suggesting that specific experience on particular stimuli rather than general experience on a wider range of stimuli may explain swine ability to solve both social and physical tasks.